Study protocol of the MUSED study: A randomized controlled trial to evaluate the psychobiological effects of group music therapy in women with depression. - Gaebel, Christine; Rittner, Sabine; Stoffel, Martin; Jarczok, Marc N.; Aguilar-Raab, Corina; Ditzen, Beate; Warth, Marco (Nordic Journal of Music Therapy, 2021)
Introduction: People suffering from depression commonly show impaired emotion regulation, accompanied by deficits in the regulation of psychobiological stress systems. Initial studies indicate that music therapy can impact depressive symptoms and psychobiological mechanisms, and may therefore contribute to effective treatment for depression. We will investigate the effects of music therapy on depressive symptoms. Moreover, we will examine the impact of this therapy on circadian biological rhythms in daily life. In particular, we will monitor the circadian rhythm of vagal tone, indexed by heart rate variability (HRV), and of the hypothalamic-pituitary-adrenal (HPA) axis, indexed by the diurnal cortisol profile, within the framework of ecological momentary assessment (EMA). Method: Seventy-four women aged 18–65 years with a diagnosis of depression or dysthymia will be eligible for participation. Participants will be randomly assigned to the intervention group (10 weeks music therapy + treatment as usual, TAU) or the control group (TAU only). Self-report data will be collected before and after the intervention period, and 10 weeks after the post-assessment. Psychobiological data (48 hours HRV, salivary cortisol from six samples each of two consecutive days) and observer ratings will be gathered before and after the intervention period. Discussion: The study aims to validate previous findings that music therapy is effective in the treatment of depression. The results will foster the understanding of how music therapy affects HPA axis and autonomic regulation processes. The EMA approach offers the potential to test for covariance between different psychobiological markers in daily life.